Institutions of General Secondary Education as Subjects of Identification of Children who are in Difficult Life Circumstances - Oleksandr Halus; Olena Halus (Pedagogical Discourse, 2021)
The article identifies the role and place of institutions of general secondary education in the mechanism of interaction of authorized entities in identifying children who are in difficult life circumstances, including children who have suffered from abuse, bullying and domestic violence. Practical recommendations for the improvement of local legal acts of institutions of secondary education on the issues of identification of children in difficult life circumstances have been developed.It is found out that it is necessary to bring local legal acts of institutions of general secondary education in line with the legislation of Ukraine in the sphere of social protection of children in difficult life circumstances.The following is proposed in institutions of general secondary education by the order of the head: to approve the instruction for employees of the educational institution on the mechanisms of identification and implementation of measures to support children who find themselves in difficult life circumstances; to approve the protocol on actions of participants of the educational process of educational institution in situations of violence; to provide in the job descriptions of pedagogical staff the responsibilities for identifying, responding in a timely manner and informing the authorized subjects about the child getting into difficult life circumstances, abuse, domestic violence, bullying; to appoint an authorized person from among the employees who will take immediate measures in case of detection of facts of violence and / or receipt of statements / notifications from the victim / other persons; to approve the composition of the standing commission for consideration of cases of bullying It is proposed to provide in the nomenclature of cases of general secondary education a log of appeals and reports regarding children in difficult life circumstances, and a log of registration of facts of detection (appeal) of domestic violence and gender-based violence (of educational institution).